2016
DOI: 10.1021/acschemneuro.6b00188
|View full text |Cite
|
Sign up to set email alerts
|

Design and Synthesis of Dimeric Securinine Analogues with Neuritogenic Activities

Abstract: Neurite outgrowth is crucial during neuronal development and regeneration, and strategies that aim at promoting neuritogenesis are beneficial for reconstructing synaptic connections after neuronal degeneration and injury. Using a bivalent analogue strategy as a successful approach, the current study identifies a series of novel dimeric securinine analogues as potent neurite outgrowth enhancers. Compounds 13, 14, 17-19, and 21-23, with different lengths of carbon chain of N,N-dialkyl substituting diacid amide l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 38 publications
1
31
1
Order By: Relevance
“…Our previous findings showed that the ability of SN3-L6 in promoting neuronal differentiation is similar to retinoic acid (RA), a well-known neuronal morphogen for potent neural fate induction ( Tang et al, 2016 ). Here, we further compared more aspects of differentiation induced by SN3-L6 and RA, and we also included another widely used neuronal differentiation inducing factor dbcAMP for the comparison ( Figure 1B ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Our previous findings showed that the ability of SN3-L6 in promoting neuronal differentiation is similar to retinoic acid (RA), a well-known neuronal morphogen for potent neural fate induction ( Tang et al, 2016 ). Here, we further compared more aspects of differentiation induced by SN3-L6 and RA, and we also included another widely used neuronal differentiation inducing factor dbcAMP for the comparison ( Figure 1B ).…”
Section: Resultsmentioning
confidence: 99%
“…We have shown that SN3-L6 is capable of inducing signaling changes at very early stages, i.e., ERK (extracellular-regulated kinase), Akt and calcium-dependent signaling activation was prominently evident at 15 min of treatment and lasted for up to 120 min ( Tang et al, 2016 ). This suggests that cellular reprogramming by SN3-L6 at early stages may be the key for differentiation induction.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations